Hydrophobic antibacterial material, preparation method and environment-friendly hydrophobic antibacterial concrete

By preparing a hydrophobic antibacterial material and combining the loading technology of polyester-based antibacterial agents and multifunctional agents, the problems of moisture penetration and antibacterial properties of concrete are solved, and the hydrophobic, anti-seepage and antibacterial properties are improved.

CN119330632AInactive Publication Date: 2025-01-21WUHAN NEW BRIGHT BUILDING MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411460708.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to its porous, multi-scale and hydrophilic properties, concrete is susceptible to external moisture and corrosive ions, affecting its performance and service life, and lacks hydrophobic and antibacterial properties.

Method used

By preparing a hydrophobic antibacterial material, 2,3-dihydroxyterephthalic hydrazide and 3-hydroxy-4-methoxybenzaldehyde are reacted to obtain an intermediate product, which is then reacted with terephthaloyl chloride to form a polyester-based antibacterial material. The agent is then reacted with 1,2-epoxyoctane to form a multifunctional agent, which is loaded on porous nanosilica through the sol-gel method. After amination treatment, a composite multifunctional agent is formed, and finally combined with the modified composite nanomaterials. Combined to prepare hydrophobic antibacterial materials.

Benefits of technology

This material not only has hydrophobic and anti-seepage properties, but can effectively reduce the water penetration of concrete and improve its mechanical and waterproof properties. It also has antibacterial properties and can maintain good antibacterial effects in dark conditions and extend the service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330632A_ABST
    Figure CN119330632A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete materials, and discloses a hydrophobic antibacterial material, a preparation method and environment-friendly hydrophobic antibacterial concrete. The preparation method of the hydrophobic antibacterial material comprises the following steps: enabling 2, 3-dihydroxy terephthalic dihydrazide to react with 3-hydroxy-4-methoxybenzaldehyde to obtain an intermediate product, and then enabling the intermediate product to react with terephthaloyl chloride and 1, 2-epoxyoctane in sequence to obtain a multifunctional agent; carrying out load modification on the multifunctional agent to obtain a modified multifunctional agent; performing surface treatment on the modified multifunctional agent to obtain an aminated modified multifunctional agent; the amination modified multifunctional agent is treated with functionalized polydimethylsiloxane, and a composite multifunctional agent is obtained; the composite multifunctional agent and the modified composite nano material are combined to obtain a hydrophobic antibacterial material, and the hydrophobic antibacterial material is added into concrete to obtain the environment-friendly hydrophobic antibacterial concrete. The environment-friendly hydrophobic antibacterial concrete disclosed by the invention has good antibacterial performance, hydrophobic anti-seepage performance and self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to a hydrophobic and antibacterial material, a preparation method, and environmentally friendly hydrophobic and antibacterial concrete. Background Art

[0002] Concrete is currently the most widely used building material, with advantages such as high strength, low cost, and wide sources of raw materials. However, due to its porous, multi-scale and hydrophilic nature, external moisture and corrosive ions can easily enter the interior of the concrete through capillary action, thus affecting the performance and service life of the concrete. In order to solve the above problems, one of the traditional methods is to form a dense protective film on the surface of the concrete by brushing or spraying to isolate the concrete from external moisture. This method has a significant waterproof effect, but it cannot achieve a hydrophobic effect. In addition, in order to prevent microbial corrosion and damage to concrete, the antibacterial property of concrete also needs to be solved. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a hydrophobic antibacterial material, comprising the following steps:

[0004] Step (1) 2,3-dihydroxyterephthaloyl hydrazide reacts with 3-hydroxy-4-methoxybenzaldehyde to obtain an intermediate product; the intermediate product reacts with terephthaloyl chloride to obtain a polyester-based antibacterial agent;

[0005] Step (2) the polyester-based antibacterial agent reacts with 1,2-octane oxide to obtain a multifunctional agent; the multifunctional agent is loaded and modified with porous nano-silica by a sol-gel method to obtain a modified multifunctional agent;

[0006] Step (3) surface treating the modified multifunctional agent with a silane coupling agent KH550 to obtain an amino-modified multifunctional agent;

[0007] Step (4) treating hydrogen-terminated polydimethylsiloxane with 2-allylsuccinic acid to obtain functionalized polydimethylsiloxane; treating the amino-modified multifunctional agent with the functionalized polydimethylsiloxane to obtain a composite multifunctional agent;

[0008] Step (5) combining the composite multifunctional agent with the modified composite nanomaterial to obtain a hydrophobic antibacterial material;

[0009] The method for preparing the modified composite nanomaterial comprises the following steps:

[0010] Step S1, using graphite powder as raw material to prepare graphene oxide;

[0011] Step S2, in-situ growing copper-doped nano zinc oxide on the surface of graphene oxide to obtain modified graphene oxide, and then calcining after treating with sodium borohydride to obtain a composite nano material;

[0012] Step S3, modifying the composite nanomaterial with 3-glycidyloxypropyltrimethoxysilane to obtain a modified composite nanomaterial.

[0013] Preferably, in step (1), the preparation method of the polyester-based antibacterial agent is:

[0014] Mix 2,3-dihydroxyterephthaloylhydrazide and acetic acid, stir for 20-40 minutes, then add 3-hydroxy-4-methoxybenzaldehyde, stir at 37-42°C and 200-300 r / min for 20-40 minutes, cool to room temperature, filter, wash, and dry to obtain an intermediate product; wherein the mass ratio of 2,3-dihydroxyterephthaloylhydrazide, acetic acid, and 3-hydroxy-4-methoxybenzaldehyde is (4.5-9):(50-100):(1.8-3.5);

[0015] In the above process, the amino group of 2,3-dihydroxyterephthaloylhydrazide reacts with the aldehyde group of 3-hydroxy-4-methoxybenzaldehyde to form an intermediate product containing multiple phenolic hydroxyl groups, aromatic rings and dynamic acylhydrazone bonds;

[0016] At 0-3°C, terephthaloyl chloride is added to N,N-dimethylformamide, and stirred for 20-40 minutes to obtain a mixed solution; in a nitrogen atmosphere, the intermediate product, N,N-dimethylformamide, and triethylamine are mixed, stirred for 20-40 minutes, and then the mixed solution is added dropwise at a rate of 1-2 mL / min, and then reacted in an oil bath at 70-90°C for 3-5 hours, the reaction is terminated with cold water, filtered, and the obtained solid is washed with a saturated sodium carbonate aqueous solution and dried to obtain a polyester-based antibacterial agent; wherein the mass ratio of terephthaloyl chloride, the intermediate product, and triethylamine is (0.4-1.2):(1.1-3.3):(0.6-1.8);

[0017] In the above process, part of the phenolic hydroxyl groups in the intermediate product undergo esterification reaction with two acyl chlorides of terephthaloyl chloride to form a polyester-based antimicrobial agent.

[0018] Preferably, in step (2), the preparation method of the modified multifunctional agent is:

[0019] Add the polyester-based antibacterial agent to ethanol, disperse it evenly by ultrasonication, add triethylamine and 1,2-epoxyoctane under stirring conditions of 200-300 r / min, heat to reflux, continue stirring and react for 6-8 hours, and after the reaction is completed, cool to room temperature, filter, wash, and dry to obtain a multifunctional agent; wherein the mass ratio of the polyester-based antibacterial agent, ethanol, triethylamine, and 1,2-epoxyoctane is (1-2):(40-60):(0.02-0.05):(0.5-1);

[0020] In the above process, the phenolic hydroxyl group in the polyester-based antimicrobial agent reacts with the epoxy group of 1,2-octane oxide, and a hydrophobic alkyl chain is introduced into the structure of the polyester-based antimicrobial agent to form a polyester-based multifunctional agent containing phenolic hydroxyl groups, aromatic rings, dynamic acylhydrazone bonds, and hydrophobic alkyl chains. The dynamic acylhydrazone bonds have self-repairing functions, and the phenolic hydroxyl groups have antibacterial properties. In addition, the N and O donor atoms in the polyester-based antimicrobial agent combine with the free OH groups in the microbial enzyme to produce antibacterial activity.

[0021] The ethanol and deionized water are mixed uniformly, heated to 35-45° C., the pH value is adjusted to 8.5-9.5 with 25 wt % ammonia water, the multifunctional agent and OP-10 are added, and then tetraethyl orthosilicate is added dropwise at a rate of 1-2 mL / min, and stirring is continued for 2-3 hours. After the reaction is completed, the pH is adjusted to neutral with a 1 mol / L hydrochloric acid aqueous solution, centrifuged and washed, and dried to obtain a modified multifunctional agent; wherein the amount ratio of ethanol, deionized water, multifunctional agent, OP-10, and tetraethyl orthosilicate is (15-35) g: (50-120) g: (1-1.5) g: (0.2-0.4) mL: (0.5-0.9) g;

[0022] In the above process, a modified multifunctional agent loaded with porous nano-silica is prepared by a sol-gel method.

[0023] Preferably, in the step (3), the preparation method of the amino modified multifunctional agent is as follows: the modified multifunctional agent is dispersed in an ethanol aqueous solution with a volume fraction of 40% at a dosage ratio of (1-2) g: (6-12) mL to obtain a dispersion of the modified multifunctional agent; the silane coupling agent KH550 and deionized water are mixed at a mass ratio of (0.1-0.5): (10-20), and the pH is adjusted to 3-4 by acetic acid, and then added to the dispersion of the modified multifunctional agent, reacted at 60-70° C. for 5-8 h, filtered, washed, and dried to obtain the amino modified multifunctional agent; wherein the mass ratio of the silane coupling agent KH550 to the modified multifunctional agent is (1-2): (0.1-0.5);

[0024] In the above process, the modified multifunctional agent is surface treated by silane coupling agent KH550, and amino groups are introduced on the surface of the modified multifunctional agent.

[0025] Preferably, in step (4), the preparation method of the composite multifunctional agent is:

[0026] 2-allylsuccinic acid and hydrogen-terminated polydimethylsiloxane are added to toluene, and then a Karstedt catalyst is added. The temperature is raised to reflux reaction for 7-9 hours in a nitrogen atmosphere. After the reaction is completed, the solvent is removed by distillation under reduced pressure. The obtained crude product is washed with methanol and toluene to obtain functionalized polydimethylsiloxane; wherein the mass ratio of 2-allylsuccinic acid, hydrogen-terminated polydimethylsiloxane, toluene, and Karstedt catalyst is (2-4):(7.5-15):(50-100):(0.5-1);

[0027] In the above process, the carbon-carbon double bond of 2-allylsuccinic acid reacts with hydrogen-terminated polydimethylsiloxane through addition reaction to form functionalized polydimethylsiloxane containing carboxyl groups;

[0028] Sodium dodecylbenzene sulfonate and functionalized polydimethylsiloxane are added to ethanol in a mass ratio of (0.05-0.1):(0.3-1):(40-60), and stirred at a speed of 500-700 r / min to form a silicone oil emulsion; an amino-modified multifunctional agent is mixed with deionized water in a mass ratio of (1-2):(30-50), and stirred at a speed of 500-700 r / min to form a suspension, and then mixed with the above silicone oil emulsion, stirred at a speed of 500-700 r / min at 60-80°C for 1.5-2.5h, and then deionized water is added and stirred for 40-80min, and the mixture is allowed to stand for precipitation for 2-5h, filtered, and dried to obtain a composite multifunctional agent; wherein the mass ratio of the functionalized polydimethylsiloxane and the amino-modified multifunctional agent is (0.3-1):(1-2);

[0029] In the above process, the amino-modified multifunctional agent and the functionalized polydimethylsiloxane are combined through the electrostatic interaction of the carboxyl group and the amino group, and the hydrophobic polydimethylsiloxane is wrapped around the amino-modified multifunctional agent to achieve the slow release of the amino-modified multifunctional agent.

[0030] Preferably, in step (5), the preparation method of the hydrophobic antibacterial material is:

[0031] The composite multifunctional agent and N,N-dimethylformamide are mixed, and ultrasonic treatment is performed for 20-40 minutes to obtain a dispersion of the composite multifunctional agent; tetrabutylammonium bromide, modified composite nanomaterials, and N,N-dimethylformamide are evenly mixed, and then mixed with the dispersion of the above composite multifunctional agent, and refluxed at 100-120°C for 2-3 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a hydrophobic antibacterial material.

[0032] Preferably, in the step (5), the mass ratio of the composite multifunctional agent to N,N-dimethylformamide in the dispersion of the composite multifunctional agent is (0.4-1.5):(20-40); the mass ratio of the composite multifunctional agent, tetrabutylammonium bromide, and modified composite nanomaterial is (0.4-1.5):(0.02-0.04):(1.5-2.5);

[0033] In the above process, the carboxyl groups on the surface of the composite multifunctional agent can react with the epoxy groups of the modified composite nanomaterial, and the composite multifunctional agent is deposited on the modified composite nanomaterial in a chemically bonded manner.

[0034] Preferably, in step (5), the preparation method of the modified composite nanomaterial is:

[0035] Step S1, 98wt% sulfuric acid and 85wt% phosphoric acid are mixed in a volume ratio of (45-50):12 to form a mixed acid solution; graphite powder is added to the mixed acid solution, stirred at a speed of 500-600r / min in an ice bath for 5-10min, then potassium permanganate is added, kept in an ice bath for 5-10min, then stirred at 30-40°C for 4-6h, deionized water is added and stirred to form a suspension, the suspension is heated to 90-100°C and kept for 2.5-3.5h, hydrogen peroxide is added, and the obtained precipitated product is washed with deionized water until the pH of the washing solution is 7, and dried to obtain graphene oxide; wherein the amount ratio of graphite powder, mixed acid solution, potassium permanganate, and hydrogen peroxide is (1-3)g:(50-200)mL:(12-24)g:(30-60)g;

[0036] In the above process, graphene oxide containing multiple hydroxyl groups and carboxyl groups is obtained by oxidizing graphite powder;

[0037] Step S2, dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion; dissolving zinc nitrate and cupric chloride in deionized water, then adding zinc oxide nanoparticles and mixing evenly, then adding a sodium hydroxide aqueous solution with a concentration of 0.04 g / mL, stirring for 10-20 minutes, mixing with the above graphene oxide dispersion, and then reacting at 80-100° C. for 5-7 hours, filtering, washing, drying, and grinding to obtain modified graphene oxide; wherein the amount ratio of graphene oxide, zinc nitrate, cupric chloride, zinc oxide nanoparticles, and sodium hydroxide aqueous solution is (1-3) g: (1.8-3.6) g: (0.05-0.1) g: (0.1-0.2) g: (30-60) mL;

[0038] The modified graphene oxide is mixed with sodium borohydride, heated to 280-320° C. in a nitrogen atmosphere, calcined for 50-100 min, washed, and dried to obtain a composite nanomaterial; wherein the mass ratio of the modified graphene oxide to the sodium borohydride is (1.5-2.5):(0.5-1.2);

[0039] In the above process, copper-doped nano-zinc oxide is in-situ grown on the surface of graphene oxide by solvent thermal-calcination method. Sodium borohydride treatment introduces more oxygen vacancies on the surface of copper-doped nano-zinc oxide in the composite nanomaterial. The hydroxyl and carboxyl groups in graphene oxide help copper-doped nano-zinc oxide to grow and distribute more evenly.

[0040] Step S3, adding 3-glycidyloxypropyltrimethoxysilane to an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3-4 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, adding the composite nanomaterial, heating in a water bath at 60-70° C., and stirring the reaction at a speed of 400-600 r / min for 20-40 min, filtering, washing, and drying to obtain a modified composite nanomaterial; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, the ethanol aqueous solution, and the composite nanomaterial is (0.05-0.15):(0.15-0.45):(0.5-2.5);

[0041] In the above process, the surface of the composite nanomaterial is modified by 3-glycidyloxypropyltrimethoxysilane, and epoxy groups are introduced into the surface of the composite nanomaterial.

[0042] The hydrophobic antibacterial material is prepared by the method for preparing the hydrophobic antibacterial material.

[0043] The invention also discloses an environmentally friendly hydrophobic antibacterial concrete, which is prepared by the following method: using waste concrete as a raw material, removing wood chips, glass and metal impurities, crushing and screening to obtain recycled aggregate with a particle size distribution of 4.75-26.5 mm; adding 40-60 parts of a polycarboxylic acid water reducer and 60-85 parts of the above-mentioned hydrophobic antibacterial material to 154-174 parts of water by weight, stirring evenly and then ultrasonically treating for 60-70 minutes to obtain a hydrophobic antibacterial material dispersion; stirring evenly 1000-1400 parts of recycled aggregate and 550-650 parts of river sand, adding the above-mentioned hydrophobic antibacterial material dispersion, fully stirring and then adding 365-400 parts of cement, and continuing to stir to obtain the environmentally friendly hydrophobic antibacterial concrete.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The composite nanomaterial of the present invention is obtained by in-situ growing copper-doped nano zinc oxide on the surface of graphene oxide and then treating it with sodium borohydride, wherein: 1) the photocatalytic bactericidal and antibacterial properties of copper-doped nano zinc oxide are significantly better than those of nano zinc oxide, and after being treated with sodium borohydride, oxygen vacancies can be generated on the surface of copper-doped nano zinc oxide, thereby improving the antibacterial effect. Even in dark conditions, superoxide free radicals generated by surface oxygen vacancies can maintain a good antibacterial effect; 2) the oxygen-containing functional groups on the surface of graphene oxide react with cement products (CSH and CH) of concrete, thereby enhancing the interfacial adhesion, thereby improving The mechanical properties of concrete are improved. At the same time, due to the nano-filling effect and the flake barrier effect, the addition of graphene oxide can extend the diffusion path of water and produce hydrated crystals in the concrete to fill the pores and cracks in the cement paste, which helps to form a denser and interconnected microstructure, minimize the presence of voids and increase the density of the cement matrix. The reduction in porosity ultimately leads to improved overall strength and impermeability of concrete. Furthermore, graphene oxide can promote the improvement of the antibacterial performance and antibacterial rate of nano-zinc oxide. Therefore, the composite nanomaterial of the present invention can improve the mechanical properties, hydrophobic anti-seepage properties and antibacterial properties of concrete.

[0046] 2. The present invention loads a multifunctional agent in a hydrophobic porous nano-silica to form a modified multifunctional agent. After the modified multifunctional agent is amino-modified, the hydrophobic functionalized polydimethylsiloxane is better cross-linked and wrapped on the surface of the modified multifunctional agent through the electrostatic effect of the amino group and the carboxyl group to obtain a composite multifunctional agent. Due to the nanofiller effect of the modified multifunctional agent and the volcanic ash reaction of the silica therein, the large capillary pores in the concrete are filled, resulting in more uniform and fewer pores, thereby reducing the permeability. In addition, some channels are also filled and blocked by the modified multifunctional agent, thereby achieving the hydrophobic effect and strength improvement of the concrete. By wrapping the functionalized polydimethylsiloxane on the modified multifunctional agent, the two interact with each other and jointly block the pore structure of the concrete, thereby making the concrete have a more stable slow-release hydrophobic effect. Moreover, after the modified multifunctional agent is released, the multifunctional agent loaded therein is also slowly released, and the antibacterial, hydrophobic and self-repairing effects of the multifunctional agent improve the antibacterial, hydrophobic and self-repairing properties of the concrete.

[0047] Furthermore, the composite multifunctional agent is deposited on the modified composite nanomaterial in a chemically bonded manner to improve the dispersibility of the composite multifunctional agent, and the two work together to give the concrete excellent mechanical strength, antibacterial properties, hydrophobicity, impermeability and self-healing properties.

[0048] 3. The environmentally friendly hydrophobic and antibacterial concrete prepared by the present invention using waste concrete as raw material as recycled aggregate realizes the reuse of resources, is more economical and environmentally friendly, and complies with the green and sustainable development strategy. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a process flow chart of the preparation method of the hydrophobic antibacterial material of the present invention;

[0050] Figure 2 It is a comparison chart of the antibacterial rate of Escherichia coli and the antibacterial rate of Staphylococcus aureus of the environmentally friendly hydrophobic antibacterial concrete of Examples 5-7 of the present invention and Comparative Examples 11-17;

[0051] Figure 3 It is a comparison diagram of water contact angle test of environmentally friendly hydrophobic antibacterial concrete of Examples 5-7 of the present invention and Comparative Examples 11-17;

[0052] Figure 4 It is a comparison chart of water seepage height test of environmentally friendly hydrophobic antibacterial concrete of Examples 5-7 of the present invention and Comparative Examples 11-17. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] This embodiment discloses a method for preparing a modified composite nanomaterial, comprising the following steps:

[0056] Step S1, 98wt% sulfuric acid and 85wt% phosphoric acid are mixed in a volume ratio of 47.5:12 to form a mixed acid solution; 2g of graphite powder is added to 125mL of the mixed acid solution, stirred at a speed of 550r / min in an ice bath for 8min, then 18g of potassium permanganate is added, kept in an ice bath for 8min, then stirred at 35°C for 5h, then 170g of deionized water is added and stirred to form a suspension, the suspension is heated to 95°C and kept for 3h, then 45g of hydrogen peroxide is added, and the obtained precipitated product is washed with deionized water until the pH of the washing solution is 7, and dried to obtain graphene oxide;

[0057] Step S2, dispersing 2g of graphene oxide in 150g of deionized water to obtain a graphene oxide dispersion; dissolving 2.7g of zinc nitrate and 0.08g of cupric chloride in 40g of deionized water, then adding 0.15g of zinc oxide nanoparticles and mixing evenly, then adding 45mL of a 0.04g / mL sodium hydroxide aqueous solution, stirring for 15min, mixing with the above graphene oxide dispersion, and then reacting at 90°C for 6h, filtering, washing the obtained solid product with deionized water and ethanol for 4 times each, and then vacuum drying at 60°C, grinding, to obtain modified graphene oxide, mixing 2g of modified graphene oxide with 0.8g of sodium borohydride, heating to 300°C in a nitrogen atmosphere, calcining for 75min, washing, and drying to obtain a composite nanomaterial;

[0058] Step S3, adding 0.1g of 3-glycidyloxypropyltrimethoxysilane to 0.3g of an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3.5 with an acetic acid aqueous solution with a concentration of 0.1mol / L, adding 1.5g of the composite nanomaterial, heating in a water bath at 65°C, and stirring the reaction at a speed of 500r / min for 30min, filtering, washing, and drying to obtain a modified composite nanomaterial.

[0059] Example 2

[0060] This embodiment discloses a method for preparing a hydrophobic antibacterial material, comprising the following steps:

[0061] Step (1) 4.5 g of 2,3-dihydroxyterephthaloylhydrazide and 50 g of acetic acid were mixed, stirred for 20 min, and then 1.8 g of 3-hydroxy-4-methoxybenzaldehyde was added, and the mixture was stirred at 37° C. and 200 r / min for 40 min, cooled to room temperature, filtered, and the obtained solid product was washed with ethanol three times and vacuum dried at 60° C. for 4 h to obtain an intermediate product;

[0062] At 0°C, 0.4 g of terephthaloyl chloride was added to 20 g of N, N-dimethylformamide, and stirred for 20 min to obtain a mixed solution; in a nitrogen atmosphere, 1.1 g of the intermediate product, 10 g of N, N-dimethylformamide, and 0.6 g of triethylamine were mixed, stirred for 20 min, and then dropped into the mixed solution at a rate of 1 mL / min, and then reacted in an oil bath at 70°C for 5 h, terminated the reaction with cold water, filtered, and the obtained solid was washed with a saturated sodium carbonate aqueous solution and vacuum dried at 70°C to obtain a polyester-based antibacterial agent;

[0063] Step (2) adding 1 g of a polyester-based antibacterial agent to 40 g of ethanol, uniformly dispersing by ultrasonication, adding 0.02 g of triethylamine and 0.5 g of 1,2-octane oxide under stirring at 200 r / min, heating to reflux, continuing to stir and react for 6 h, cooling to room temperature after the reaction is completed, filtering, washing the obtained solid product with ethanol three times, and vacuum drying at 60 ° C for 5 h to obtain a multifunctional agent;

[0064] 15g of ethanol and 50g of deionized water were mixed evenly, heated to 35°C, the pH value was adjusted to 8.5 with 25wt% ammonia water, 1g of multifunctional agent and 0.2mL of OP-10 were added, and 0.5g of tetraethyl orthosilicate was added dropwise at a rate of 1mL / min, and stirring was continued for 2h. After the reaction was completed, the pH was adjusted to neutral with a 1mol / L hydrochloric acid aqueous solution, centrifuged and washed, and dried at 50°C for 8h to obtain a modified multifunctional agent;

[0065] Step (3) dispersing 1 g of the modified multifunctional agent into 6 mL of 40% by volume ethanol aqueous solution to obtain a dispersion of the modified multifunctional agent; dissolving 0.1 g of silane coupling agent KH550 into 10 g of deionized water, adjusting the pH to 3 with acetic acid, and then adding the mixture to the dispersion of the modified multifunctional agent, reacting at 60° C. for 8 h, filtering, washing, and drying to obtain an amino-modified multifunctional agent;

[0066] Step (4) adding 2 g of 2-allylsuccinic acid and 7.5 g of hydrogen-terminated polydimethylsiloxane to 50 g of toluene, and then adding 0.5 g of Karstedt catalyst, heating to reflux reaction for 7 h in a nitrogen atmosphere, and after the reaction is completed, removing the solvent by reduced pressure distillation at 80° C., and washing the obtained crude product with methanol and toluene to obtain functionalized polydimethylsiloxane;

[0067] 0.05 g of sodium dodecylbenzene sulfonate and 0.3 g of functionalized polydimethylsiloxane were added to 40 g of ethanol, and stirred at a speed of 500 r / min to form a silicone oil emulsion; 1 g of amino-modified multifunctional agent was dispersed in 30 g of deionized water, and stirred at a speed of 500 r / min to form a suspension, and then mixed with the above silicone oil emulsion, stirred at a speed of 500 r / min at 60°C for 2.5 h, and then 10 g of deionized water was added and stirred for 40 min, and then allowed to settle for 2 h, filtered, and dried to obtain a composite multifunctional agent;

[0068] Step (5) 0.4 g of the composite multifunctional agent and 20 g of N,N-dimethylformamide are mixed, and ultrasonic treatment is performed for 20 min to obtain a dispersion of the composite multifunctional agent; 0.02 g of tetrabutylammonium bromide, 1.5 g of the modified composite nanomaterial, and 20 g of N,N-dimethylformamide are evenly mixed, and then mixed with the dispersion of the composite multifunctional agent, and refluxed at 100° C. for 3 h. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a hydrophobic antibacterial material.

[0069] Example 3

[0070] This embodiment discloses a method for preparing a hydrophobic antibacterial material, comprising the following steps:

[0071] Step (1) 9 g of 2,3-dihydroxyterephthaloylhydrazide and 100 g of acetic acid were mixed, stirred for 40 min, and then 3.5 g of 3-hydroxy-4-methoxybenzaldehyde was added, and the mixture was stirred at 42° C. and 300 r / min for 20 min, cooled to room temperature, filtered, and the obtained solid product was washed with ethanol 5 times, and then vacuum dried at 80° C. for 2 h to obtain an intermediate product;

[0072] At 3°C, 1.2 g of terephthaloyl chloride was added to 50 g of N, N-dimethylformamide and stirred for 40 min to obtain a mixed solution; in a nitrogen atmosphere, 3.3 g of the intermediate product, 30 g of N, N-dimethylformamide and 1.8 g of triethylamine were mixed and stirred for 40 min, and then the mixed solution was added dropwise at a rate of 2 mL / min, and then reacted in an oil bath at 90°C for 3 h, the reaction was terminated with cold water, filtered, and the obtained solid was washed with a saturated sodium carbonate aqueous solution and vacuum dried at 80°C to obtain a polyester-based antibacterial agent;

[0073] Step (2) adding 2 g of a polyester-based antibacterial agent to 60 g of ethanol, uniformly dispersing by ultrasonication, adding 0.05 g of triethylamine and 1 g of 1,2-octane oxide under stirring at 300 r / min, heating to reflux, continuing to stir and react for 8 h, cooling to room temperature after the reaction is completed, filtering, washing the obtained solid product with ethanol 5 times, and vacuum drying at 80 ° C for 5 h to obtain a multifunctional agent;

[0074] 35g of ethanol and 120g of deionized water were mixed evenly, heated to 45°C, the pH value was adjusted to 9.5 with 25wt% ammonia water, 1.5g of multifunctional agent and 0.4mL of OP-10 were added, and 0.9g of tetraethyl orthosilicate was added dropwise at a rate of 2mL / min, and stirring was continued for 3h. After the reaction was completed, the pH was adjusted to neutral with a 1mol / L hydrochloric acid aqueous solution, centrifuged and washed, and dried at 60°C for 6h to obtain a modified multifunctional agent;

[0075] Step (3) dispersing 2 g of the modified multifunctional agent into 12 mL of 40% by volume ethanol aqueous solution to obtain a dispersion of the modified multifunctional agent; dissolving 0.5 g of silane coupling agent KH550 into 20 g of deionized water, adjusting the pH to 4 with acetic acid, and then adding the mixture to the dispersion of the modified multifunctional agent, reacting at 70° C. for 5 h, filtering, washing, and drying to obtain an amino-modified multifunctional agent;

[0076] Step (4) adding 4 g of 2-allylsuccinic acid and 15 g of hydrogen-terminated polydimethylsiloxane to 100 g of toluene, and then adding 1 g of Karstedt catalyst, heating to reflux reaction for 9 h in a nitrogen atmosphere, after the reaction is completed, removing the solvent by reduced pressure distillation at 90° C., and washing the obtained crude product with methanol and toluene to obtain functionalized polydimethylsiloxane;

[0077] 0.1g sodium dodecylbenzene sulfonate and 1g functionalized polydimethylsiloxane were added to 60g ethanol, and stirred at a speed of 700r / min to form a silicone oil emulsion; 2g amino modified multifunctional agent was dispersed in 50g deionized water, and stirred at a speed of 700r / min to form a suspension, and then mixed with the above silicone oil emulsion, stirred at 80°C at a speed of 700r / min for 1.5h, and then 20g deionized water was added and stirred for 80min, and then allowed to settle for 5h, filtered, and dried to obtain a composite multifunctional agent;

[0078] Step (5) 1.5 g of the composite multifunctional agent and 40 g of N,N-dimethylformamide are mixed, and ultrasonic treatment is performed for 40 min to obtain a dispersion of the composite multifunctional agent; 0.04 g of tetrabutylammonium bromide, 2.5 g of the modified composite nanomaterial, and 40 g of N,N-dimethylformamide are evenly mixed, and then mixed with the dispersion of the composite multifunctional agent, and refluxed at 120° C. for 2 h. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a hydrophobic antibacterial material.

[0079] Example 4

[0080] This embodiment discloses a method for preparing a hydrophobic antibacterial material, comprising the following steps:

[0081] Step (1) 6.3 g of 2,3-dihydroxyterephthaloylhydrazide and 75 g of acetic acid were mixed, stirred for 30 min, and then 2.7 g of 3-hydroxy-4-methoxybenzaldehyde was added, and the mixture was stirred at 40° C. and 250 r / min for 30 min, cooled to room temperature, filtered, and the obtained solid product was washed with ethanol 4 times, and then vacuum dried at 70° C. for 3 h to obtain an intermediate product;

[0082] At 2°C, 0.8 g of terephthaloyl chloride was added to 35 g of N, N-dimethylformamide, and stirred for 30 min to obtain a mixed solution; in a nitrogen atmosphere, 2.2 g of the intermediate product, 20 g of N, N-dimethylformamide, and 1.2 g of triethylamine were mixed, stirred for 30 min, and then dropped into the mixed solution at a rate of 1.5 mL / min, and then reacted in an oil bath at 80°C for 4 h, terminated the reaction with cold water, filtered, and the obtained solid was washed with a saturated sodium carbonate aqueous solution and vacuum dried at 75°C to obtain a polyester-based antibacterial agent;

[0083] Step (2) adding 1.5 g of a polyester-based antibacterial agent to 50 g of ethanol, uniformly dispersing by ultrasonication, adding 0.04 g of triethylamine and 0.8 g of 1,2-octane oxide under stirring at 250 r / min, heating to reflux, and continuing to stir and react for 7 h. After the reaction is completed, cooling to room temperature and filtering are performed. The obtained solid product is washed with ethanol 4 times and then vacuum dried at 70 ° C for 6 h to obtain a multifunctional agent;

[0084] 25g of ethanol and 85g of deionized water were mixed evenly, heated to 40°C, the pH value was adjusted to 9 with 25wt% ammonia water, 1.3g of multifunctional agent and 0.3mL of OP-10 were added, and 0.7g of tetraethyl orthosilicate was added dropwise at a rate of 1.5mL / min, and stirring was continued for 2.5h. After the reaction was completed, the pH was adjusted to neutral with a 1mol / L hydrochloric acid aqueous solution, centrifuged and washed, and dried at 55°C for 7h to obtain a modified multifunctional agent;

[0085] Step (3) dispersing 1.5 g of the modified multifunctional agent into 9 mL of 40% by volume ethanol aqueous solution to obtain a dispersion of the modified multifunctional agent; dissolving 0.3 g of silane coupling agent KH550 into 15 g of deionized water, adjusting the pH to 3.5 with acetic acid, and then adding the mixture to the dispersion of the modified multifunctional agent, reacting at 65° C. for 6.5 h, filtering, washing, and drying to obtain an amino-modified multifunctional agent;

[0086] Step (4) adding 3 g of 2-allylsuccinic acid and 11.3 g of hydrogen-terminated polydimethylsiloxane to 75 g of toluene, and then adding 0.8 g of Karstedt catalyst, heating to reflux reaction for 8 h in a nitrogen atmosphere, after the reaction is completed, removing the solvent by reduced pressure distillation at 85° C., and washing the obtained crude product with methanol and toluene to obtain functionalized polydimethylsiloxane;

[0087] 0.08g of sodium dodecylbenzene sulfonate and 0.6g of functionalized polydimethylsiloxane were added to 50g of ethanol, and stirred at a speed of 600r / min to form a silicone oil emulsion; 1.5g of amino-modified multifunctional agent was dispersed in 40g of deionized water, and stirred at a speed of 600r / min to form a suspension, and then mixed with the above silicone oil emulsion, stirred at a speed of 600r / min at 70°C for 2h, and then 15g of deionized water was added and stirred for 60min, and then allowed to settle for 4h, filtered, and dried to obtain a composite multifunctional agent;

[0088] Step (5) 0.8 g of the composite multifunctional agent and 30 g of N,N-dimethylformamide are mixed, and ultrasonic treatment is performed for 30 min to obtain a dispersion of the composite multifunctional agent; 0.03 g of tetrabutylammonium bromide, 2 g of the modified composite nanomaterial, and 30 g of N,N-dimethylformamide are evenly mixed, and then mixed with the dispersion of the composite multifunctional agent, and refluxed at 110° C. for 2.5 h. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a hydrophobic antibacterial material.

[0089] Example 5

[0090] This embodiment discloses a method for preparing environmentally friendly hydrophobic antibacterial concrete, comprising the following steps:

[0091] Waste concrete is used as raw material, wood chips, glass and metal impurities are removed, crushed and sieved to obtain recycled aggregate with a particle size distribution of 4.75-26.5 mm; 40 parts of polycarboxylic acid water reducer and 60 parts of hydrophobic antibacterial material are added to 154 parts of water by weight, stirred evenly and then ultrasonically treated for 60 minutes to obtain a hydrophobic antibacterial material dispersion; 1000 parts of recycled aggregate and 550 parts of river sand are stirred evenly, and then the hydrophobic antibacterial material dispersion is added, and after fully stirring, 365 parts of cement are added, and stirring is continued to obtain environmentally friendly hydrophobic antibacterial concrete.

[0092] Example 6

[0093] This embodiment discloses a method for preparing environmentally friendly hydrophobic antibacterial concrete, comprising the following steps:

[0094] Waste concrete is used as raw material, wood chips, glass and metal impurities are removed, crushed and sieved to obtain recycled aggregate with a particle size distribution of 4.75-26.5 mm; 60 parts of polycarboxylic acid water reducer and 85 parts of hydrophobic antibacterial material are added to 174 parts of water by weight, stirred evenly and ultrasonically treated for 70 minutes to obtain a hydrophobic antibacterial material dispersion; 1400 parts of recycled aggregate and 650 parts of river sand are stirred evenly, and then the hydrophobic antibacterial material dispersion is added, and after fully stirring, 400 parts of cement are added and stirred continuously to obtain environmentally friendly hydrophobic antibacterial concrete.

[0095] Example 7

[0096] This embodiment discloses a method for preparing environmentally friendly hydrophobic antibacterial concrete, comprising the following steps:

[0097] Using waste concrete as raw material, remove wood chips, glass, and metal impurities, crush, and sieve to obtain recycled aggregate with a particle size distribution of 4.75-26.5 mm; by weight, add 50 parts of polycarboxylic acid water reducer and 75 parts of hydrophobic antibacterial material to 164 parts of water, stir evenly, and then ultrasonically treat for 65 minutes to obtain a hydrophobic antibacterial material dispersion; stir 1200 parts of recycled aggregate and 600 parts of river sand evenly, add the above-mentioned hydrophobic antibacterial material dispersion, stir thoroughly, then add 388 parts of cement, and continue stirring to obtain environmentally friendly hydrophobic antibacterial concrete.

[0098] The modified composite nanomaterials in the above Examples 2-4 adopt the modified composite nanomaterials prepared in Example 1; the hydrophobic antibacterial materials in Examples 5-7 adopt the hydrophobic antibacterial materials prepared in Example 4.

[0099] Comparative Example 1

[0100] Comparative Example 1 Compared with Example 1, in the process of preparing the composite nanomaterial in Comparative Example 1, graphene oxide was not added, and other conditions remained unchanged.

[0101] Comparative Example 2

[0102] Comparative Example 2 Compared with Example 1, in the process of preparing the composite nanomaterial in Comparative Example 2, no copper chloride was added, and other conditions remained unchanged.

[0103] Comparative Example 3

[0104] Comparative Example 3 Compared with Example 1, during the preparation of the composite nanomaterial, Comparative Example 3 was not treated with sodium borohydride, and other conditions remained unchanged.

[0105] Comparative Example 4

[0106] Comparative Example 4 Compared with Example 4, in the process of preparing the hydrophobic antibacterial material, Comparative Example 4 uses the modified composite nanomaterial prepared in Comparative Example 1, and other conditions remain unchanged.

[0107] Comparative Example 5

[0108] Comparative Example 5 Compared with Example 4, in the process of preparing the hydrophobic antibacterial material, Comparative Example 5 uses the modified composite nanomaterial prepared in Comparative Example 2, and other conditions remain unchanged.

[0109] Comparative Example 6

[0110] Comparative Example 6 Compared with Example 4, in the process of preparing the hydrophobic antibacterial material, Comparative Example 6 uses the modified composite nanomaterial prepared in Comparative Example 3, and other conditions remain unchanged.

[0111] Comparative Example 7

[0112] Compared with Example 4, in Comparative Example 7, during the preparation of the modified multifunctional agent, a polyester-based antibacterial agent was used instead of the multifunctional agent, and other conditions remained unchanged.

[0113] Comparative Example 8

[0114] Compared with Example 4, in Comparative Example 8, during the preparation of the modified multifunctional agent, no multifunctional agent was added (ie, the modified multifunctional agent in this comparative example was porous nano-silica), and other conditions remained unchanged.

[0115] Comparative Example 9

[0116] Compared with Example 4, in Comparative Example 9, during the preparation of the amino-modified multifunctional agent, the modified multifunctional agent was replaced by the multifunctional agent, and other conditions remained unchanged.

[0117] Comparative Example 10

[0118] Compared with Example 4, in Comparative Example 10, during the preparation of the hydrophobic antibacterial material, the amino-modified multifunctional agent was used instead of the composite multifunctional agent, and other conditions remained unchanged.

[0119] Comparative Example 11

[0120] Compared with Example 7, the environmentally friendly hydrophobic and antibacterial concrete of Comparative Example 11 adopts the hydrophobic and antibacterial material of Comparative Example 4, and other conditions remain unchanged.

[0121] Comparative Example 12

[0122] Comparative Example 12 Compared with Example 7, the environmentally friendly hydrophobic and antibacterial concrete of Comparative Example 12 adopts the hydrophobic and antibacterial material of Comparative Example 5, and other conditions remain unchanged.

[0123] Comparative Example 13

[0124] Comparative Example 13 Compared with Example 7, the environmentally friendly hydrophobic antibacterial concrete of Comparative Example 13 adopts the hydrophobic antibacterial material of Comparative Example 6, and other conditions remain unchanged.

[0125] Comparative Example 14

[0126] Comparative Example 14 Compared with Example 7, the environmentally friendly hydrophobic and antibacterial concrete of Comparative Example 14 adopts the hydrophobic and antibacterial material of Comparative Example 7, and other conditions remain unchanged.

[0127] Comparative Example 15

[0128] Comparative Example 15 Compared with Example 7, the environmentally friendly hydrophobic and antibacterial concrete of Comparative Example 15 adopts the hydrophobic and antibacterial material of Comparative Example 8, and other conditions remain unchanged.

[0129] Comparative Example 16

[0130] Comparative Example 16 Compared with Example 7, the environmentally friendly hydrophobic antibacterial concrete of Comparative Example 16 adopts the hydrophobic antibacterial material of Comparative Example 9, and other conditions remain unchanged.

[0131] Comparative Example 17

[0132] Comparative Example 11 Compared with Example 7, the environmentally friendly hydrophobic and antibacterial concrete of Comparative Example 17 adopts the hydrophobic and antibacterial material of Comparative Example 10, and other conditions remain unchanged.

[0133] In the above embodiments and comparative examples, graphite powder, with an effective ingredient content of 99.99%, a particle size / mesh of 12500 mesh, a particle size of 7-12um under the sieve, and a particle size of 20um over the sieve, is from Hebei Wenlun Metal Materials Co., Ltd.; ZnO nanoparticles, with a zinc content of ≥99.9%, irregular shape, and a particle size of 50nm, are from Qinghe County Ruijiang Metal Materials Co., Ltd.; OP-10, with an effective ingredient content of 99%, a light yellow to yellow oily liquid, and a pH value of 5 to 7, is from Tianjin Red Sun Chemical Co., Ltd.; 2-allylsuccinic acid, CAS: 5754-10-9, purity: ≥95%, is from Shaoyuan Technology (Shanghai) Co., Ltd.; Karstedt catalyst, properties: colorless to light yellow transparent liquid, density of 1.0±0.1g / cm 3 , melting point is -44℃, from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; hydrogen-terminated polydimethylsiloxane, average molecular weight is about 580Da, from Sigma-Aldrich Chemical Co.; polycarboxylate water reducer, solid content is 25%, water reduction rate is 30%, from Jiangsu Bote New Materials Co., Ltd.; cement is P.O42.5 ordinary Portland cement, density is 3150kg / m 3 , from China Resources Cement Holdings Co., Ltd.; river sand, apparent density is 2600kg / m 3 , mud content 0.4%, fineness modulus 2.7, purchased from Taixing Sand and Gravel Factory, Jiangsu Province.

[0134] Experimental example

[0135] The performance test was conducted on the environmentally friendly hydrophobic antibacterial concrete of Examples 5-7 and Comparative Examples 11-17 (a blank control group was set up, and no hydrophobic antibacterial material was added to the blank control group).

[0136] 1. Antibacterial performance test: According to the preparation method of environmentally friendly hydrophobic antibacterial concrete of Examples 5-7 and Comparative Examples 11-17, cement concrete specimens with a diameter of 10 cm and a thickness of 2 cm were respectively produced and processed. After the specimens were cured for 28 days, Staphylococcus aureus and Escherichia coli were used as test bacteria to determine the antibacterial effect. First, 75% ethanol solution was used to disinfect the surface of the specimens, then rinsed and soaked with sterile distilled water until constant weight, and then placed in an ultra-clean transparent box at a constant temperature and humidity of 32°C for use. 2 mL of 10 5 cfu / mL of bacterial solution was inoculated on the surface of each specimen, and a xenon lamp was placed directly above the specimen to irradiate. After irradiating the specimen inoculated with bacterial solution for 60 minutes, the count was performed under a microscope, and the antibacterial rate of the specimen was determined by the percentage difference in the number of colonies compared with that of comparative example 2. i :

[0137] ν i =(mm i ) / m×100%;

[0138] m is the number of colonies in the blank control group after illumination; m i Respectively represent the colony counts of each embodiment and comparative example sample after illumination.

[0139] 2. Hydrophobicity test: Use a contact angle meter to conduct a contact angle test on the environmentally friendly hydrophobic and antibacterial concrete.

[0140] 3. Anti-seepage performance test: The test is carried out in accordance with the test method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", with a penetration pressure of 3.5MPa and a pressurization time of 48h.

[0141] The test results are shown in Table 1:

[0142] Table 1

[0143]

[0144] It can be seen from the test results in Table 1 that the environmentally friendly hydrophobic antibacterial concrete prepared in Examples 2-4 of the present invention has excellent antibacterial and hydrophobic anti-seepage properties. From the comparison of Comparative Example 11 with Example 7, it can be seen that graphene oxide can enhance the interfacial adhesion, and at the same time, due to the nano-filling effect and the sheet barrier effect, the anti-seepage property is improved, and graphene oxide can promote the improvement of the antibacterial performance and antibacterial rate of nano zinc oxide, thereby improving the hydrophobic anti-seepage and antibacterial properties of concrete; from the comparison of Comparative Examples 12-13 with Example 7, it can be seen that the photocatalytic bactericidal and antibacterial properties of copper-doped nano zinc oxide are significantly better than those of nano zinc oxide, and after being treated with sodium borohydride, oxygen vacancies can be generated on the surface of copper-doped nano zinc oxide to improve the antibacterial effect; from the comparison of Comparative Example 14 with Example 7, it can be seen that 1,2-octane oxide A hydrophobic alkyl chain is introduced into the structure of the multifunctional agent to improve the hydrophobic and anti-seepage properties of the concrete. From the comparison between comparative example 15 and example 7, it can be seen that the multifunctional agent of the present invention has antibacterial, hydrophobic and anti-seepage effects. From the comparison between comparative examples 16-17 and example 7, it can be seen that due to the nanofiller effect of the modified multifunctional agent and the volcanic ash reaction of silica therein, the large capillaries in the concrete are filled, thereby achieving the hydrophobic and anti-seepage effect of the concrete. By wrapping the functionalized polydimethylsiloxane on the modified multifunctional agent, the two interact with each other and jointly block the pore structure of the concrete, thereby making the concrete have better hydrophobic and anti-seepage effects.

[0145] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a hydrophobic antibacterial material, characterized in that: The following steps are involved: Step (1) 2,3-dihydroxyterephthaloyl hydrazide reacts with 3-hydroxy-4-methoxybenzaldehyde to obtain an intermediate product; the intermediate product reacts with terephthaloyl chloride to obtain a polyester-based antibacterial agent; Step (2) the polyester-based antibacterial agent reacts with 1,2-octane oxide to obtain a multifunctional agent; the multifunctional agent is loaded and modified with porous nano-silica by a sol-gel method to obtain a modified multifunctional agent; Step (3) surface treating the modified multifunctional agent with a silane coupling agent KH550 to obtain an amino-modified multifunctional agent; Step (4) treating hydrogen-terminated polydimethylsiloxane with 2-allylsuccinic acid to obtain functionalized polydimethylsiloxane; treating the amino-modified multifunctional agent with the functionalized polydimethylsiloxane to obtain a composite multifunctional agent; Step (5) combining the composite multifunctional agent with the modified composite nanomaterial to obtain a hydrophobic antibacterial material; The method for preparing the modified composite nanomaterial comprises the following steps: Step S1, using graphite powder as raw material to prepare graphene oxide; Step S2, in-situ growing copper-doped nano zinc oxide on the surface of graphene oxide to obtain modified graphene oxide, and then calcining after treating with sodium borohydride to obtain a composite nano material; Step S3, modifying the composite nanomaterial with 3-glycidyloxypropyltrimethoxysilane to obtain a modified composite nanomaterial.

2. The method for preparing the hydrophobic antibacterial material according to claim 1, characterized in that: In the step (1), the preparation method of the polyester-based antibacterial agent is: Mix 2,3-dihydroxyterephthaloylhydrazide and acetic acid, stir for 20-40 minutes, then add 3-hydroxy-4-methoxybenzaldehyde, stir at 37-42°C and 200-300 r / min for 20-40 minutes, cool to room temperature, filter, wash, and dry to obtain an intermediate product; wherein the mass ratio of 2,3-dihydroxyterephthaloylhydrazide, acetic acid, and 3-hydroxy-4-methoxybenzaldehyde is (4.5-9):(50-100):(1.8-3.5); At 0-3°C, terephthaloyl chloride is added to N,N-dimethylformamide, and stirred for 20-40 minutes to obtain a mixed solution; in a nitrogen atmosphere, the intermediate product, N,N-dimethylformamide and triethylamine are mixed, stirred for 20-40 minutes, and then the mixed solution is dropped at a rate of 1-2 mL / min, and then reacted in an oil bath at 70-90°C for 3-5 hours, the reaction is terminated with cold water, filtered, and the obtained solid is washed with a saturated sodium carbonate aqueous solution and dried to obtain a polyester-based antibacterial agent; wherein the mass ratio of terephthaloyl chloride, the intermediate product and triethylamine is (0.4-1.2):(1.1-3.3):(0.6-1.8).

3. The method for preparing the hydrophobic antibacterial material according to claim 1, characterized in that: In the step (2), the preparation method of the modified multifunctional agent is: Add the polyester-based antibacterial agent to ethanol, disperse it evenly by ultrasonication, add triethylamine and 1,2-epoxyoctane under stirring conditions of 200-300 r / min, heat to reflux, continue stirring and react for 6-8 hours, and after the reaction is completed, cool to room temperature, filter, wash, and dry to obtain a multifunctional agent; wherein the mass ratio of the polyester-based antibacterial agent, ethanol, triethylamine, and 1,2-epoxyoctane is (1-2):(40-60):(0.02-0.05):(0.5-1); Ethanol and deionized water are mixed evenly, heated to 35-45° C., the pH value is adjusted to 8.5-9.5 with 25 wt % ammonia water, a multifunctional agent and OP-10 are added, and then tetraethyl orthosilicate is added dropwise at a rate of 1-2 mL / min, and stirring is continued for 2-3 hours. After the reaction is completed, the pH is adjusted to neutral with a 1 mol / L hydrochloric acid aqueous solution, centrifuged and washed, and dried to obtain a modified multifunctional agent; wherein the amount ratio of ethanol, deionized water, multifunctional agent, OP-10, and tetraethyl orthosilicate is (15-35) g: (50-120) g: (1-1.5) g: (0.2-0.4) mL: (0.5-0.9) g.

4. The method for preparing the hydrophobic antibacterial material according to claim 1, characterized in that: In the step (3), the preparation method of the amino modified multifunctional agent is as follows: the modified multifunctional agent is dispersed in an ethanol aqueous solution with a volume fraction of 40% at a dosage ratio of (1-2) g: (6-12) mL to obtain a dispersion of the modified multifunctional agent; the silane coupling agent KH550 and deionized water are mixed at a mass ratio of (0.1-0.5): (10-20), and the pH is adjusted to 3-4 by acetic acid, and then added to the dispersion of the modified multifunctional agent, reacted at 60-70°C for 5-8h, filtered, washed, and dried to obtain the amino modified multifunctional agent; wherein the mass ratio of the silane coupling agent KH550 to the modified multifunctional agent is (1-2): (0.1-0.5).

5. The method for preparing the hydrophobic antibacterial material according to claim 1, characterized in that: In the step (4), the preparation method of the composite multifunctional agent is: 2-allylsuccinic acid and hydrogen-terminated polydimethylsiloxane are added to toluene, and then a Karstedt catalyst is added. The temperature is raised to reflux reaction for 7-9 hours in a nitrogen atmosphere. After the reaction is completed, the solvent is removed by distillation under reduced pressure. The obtained crude product is washed with methanol and toluene to obtain functionalized polydimethylsiloxane; wherein the mass ratio of 2-allylsuccinic acid, hydrogen-terminated polydimethylsiloxane, toluene, and Karstedt catalyst is (2-4):(7.5-15):(50-100):(0.5-1); Sodium dodecylbenzene sulfonate and functionalized polydimethylsiloxane are added to ethanol in a mass ratio of (0.05-0.1):(0.3-1):(40-60), and stirred at a speed of 500-700r / min to form a silicone oil emulsion; an amino-modified multifunctional agent is mixed with deionized water in a mass ratio of (1-2):(30-50), and stirred at a speed of 500-700r / min to form a suspension, which is then mixed with the above-mentioned silicone oil emulsion, stirred at a speed of 500-700r / min at 60-80°C for 1.5-2.5h, and then deionized water is added and stirred for 40-80min, and the mixture is allowed to stand for precipitate for 2-5h, filtered, and dried to obtain a composite multifunctional agent; wherein the mass ratio of the functionalized polydimethylsiloxane and the amino-modified multifunctional agent is (0.3-1):(1-2).

6. The method for preparing the hydrophobic antibacterial material according to claim 1, characterized in that: In the step (5), the preparation method of the hydrophobic antibacterial material is: The composite multifunctional agent and N,N-dimethylformamide are mixed, and ultrasonic treatment is performed for 20-40 minutes to obtain a dispersion of the composite multifunctional agent; tetrabutylammonium bromide, modified composite nanomaterials, and N,N-dimethylformamide are evenly mixed, and then mixed with the dispersion of the composite multifunctional agent, and refluxed at 100-120°C for 2-3 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a hydrophobic antibacterial material.

7. The method for preparing a hydrophobic antibacterial material according to claim 1, characterized in that: In the step (5), the mass ratio of the composite multifunctional agent to N,N-dimethylformamide in the dispersion of the composite multifunctional agent is (0.4-1.5):(20-40); the mass ratio of the composite multifunctional agent, tetrabutylammonium bromide, and modified composite nanomaterial is (0.4-1.5):(0.02-0.04):(1.5-2.5).

8. The method for preparing a hydrophobic antibacterial material according to claim 1, characterized in that: In the step (5), the preparation method of the modified composite nanomaterial is: Step S1, 98wt% sulfuric acid and 85wt% phosphoric acid are mixed in a volume ratio of (45-50):12 to form a mixed acid solution; graphite powder is added to the mixed acid solution, stirred at a speed of 500-600r / min in an ice bath for 5-10min, then potassium permanganate is added, kept in an ice bath for 5-10min, then stirred at 30-40°C for 4-6h, deionized water is added and stirred to form a suspension, the suspension is heated to 90-100°C and kept for 2.5-3.5h, hydrogen peroxide is added, and the obtained precipitated product is washed with deionized water until the pH of the washing solution is 7, and dried to obtain graphene oxide; wherein the amount ratio of graphite powder, mixed acid solution, potassium permanganate, and hydrogen peroxide is (1-3)g:(50-200)mL:(12-24)g:(30-60)g; Step S2, dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion; dissolving zinc nitrate and cupric chloride in deionized water, then adding zinc oxide nanoparticles and mixing evenly, then adding a sodium hydroxide aqueous solution with a concentration of 0.04 g / mL, stirring for 10-20 minutes, mixing with the above graphene oxide dispersion, and then reacting at 80-100° C. for 5-7 hours, filtering, washing, drying, and grinding to obtain modified graphene oxide; wherein the amount ratio of graphene oxide, zinc nitrate, cupric chloride, zinc oxide nanoparticles, and sodium hydroxide aqueous solution is (1-3) g: (1.8-3.6) g: (0.05-0.1) g: (0.1-0.2) g: (30-60) mL; The modified graphene oxide is mixed with sodium borohydride, heated to 280-320° C. in a nitrogen atmosphere, calcined for 50-100 min, washed, and dried to obtain a composite nanomaterial; wherein the mass ratio of the modified graphene oxide to the sodium borohydride is (1.5-2.5):(0.5-1.2); Step S3, adding 3-glycidyloxypropyltrimethoxysilane to an ethanol aqueous solution with a volume fraction of 90%, adjusting the pH to 3-4 with an acetic acid aqueous solution with a concentration of 0.1 mol / L, adding the composite nanomaterial, heating in a water bath at 60-70°C, and stirring the reaction at a speed of 400-600 r / min for 20-40 min, filtering, washing, and drying to obtain a modified composite nanomaterial; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, the ethanol aqueous solution, and the composite nanomaterial is (0.05-0.15):(0.15-0.45):(0.5-2.5).

9. A hydrophobic antibacterial material prepared by the method for preparing a hydrophobic antibacterial material according to any one of claims 1 to 8.

10. An environmentally friendly hydrophobic antibacterial concrete, characterized in that: The obtained product is prepared by the following method: using waste concrete as raw material, removing wood chips, glass and metal impurities, crushing and sieving to obtain recycled aggregate with a particle size distribution of 4.75-26.5 mm; mixing 40-60 parts of polycarboxylate water reducer and 60-85 parts of The hydrophobic and antibacterial material according to claim 9 is added to 154-174 parts of water, stirred evenly, and then ultrasonically treated for 60-70 minutes to obtain a hydrophobic and antibacterial material dispersion; 1000-1400 parts of recycled aggregate and 550-650 parts of river sand are stirred evenly, and then the above-mentioned hydrophobic and antibacterial material dispersion is added, and after sufficient stirring, 365-400 parts of cement are added, and stirring is continued to obtain environmentally friendly hydrophobic and antibacterial concrete.

Citation Information

Cited By

  • Hydrophobic and oleophobic circuit board for tobacco tar-resistant microphone and preparation method of hydrophobic and oleophobic circuit board

    CN121182364A

  • Wear-resistant coating, preparation method and application of wear-resistant coating to alumite color layer

    CN121293870A